Chronic Arterial Diseases Atherosclerosis and Heart Diseases - Madinabonu Abdurakhmonova Olim kizi (Genius Journals, 2022)
This article provides information on the timely diagnosis and quality of treatment of diseases that cause atherosclerosis.
Keywords: Atherosclerosis; Blood Pressure; Artery Wall; Adipose Tissue